Drevesne smole iz stročnic (Leguminosae- Caesalpinioideae). Kaj je "dizelsko gorivo"? - Torelli, Niko (Les (Ljubljana), 2001)
An review is given of the sources, harvesting, properties and uses of tree resins from the Leguminosae: cativo balsam (Prioria copaifera), copaiba balsam(Copaifera spp.), East African copal (Trachylobium verrucosum), illurin balsam (Paradaniellia oliveri), South American copal (Hymenea coubaril), tchitola balsam (Oxystigma oxyphyllum), tolabranca balsam (Gossweilerodendron balsamiferum), tolu balsam (Myroxylon balsamum), walaba resin (Eperua falcata), West African copals (Guibourtia spp.). The anatomical basis of tree exudates is described. Trees as a source of energy are considered. Nobel laureate M. Calvin reported that oleoresin copaiba obtained by drilling holes into Copaifera lansdorfii and C. multijuga ("diesel trees" trunks can be a source of diesel fuel.
Keywords: smole; balzami; stročnice